ТҮРКИЙ ХАЛЫҚЛАР РУЎҲЫЙ-ӘДЕБИЙ ӘЛЕМИНИҢ ЖАРЫҚ ЖУЛДЫЗЫ - Алламбергенов, К. (FAN va JAMIYAT, 2022)
The article talks about the life and work of Hakim father Sulayman Boqirgani, who lived in the Karakalpak region. In particular, Sulayman Bakirgani’s contribution to the spread of Sufism as a student of Khoja Ahmed Yassavi, as well as his religious and literary works, are extensively analyzed.